Inclusive development in environmental sustainability in sub-Saharan Africa: Insights from governance mechanisms - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
This research examines the relevance of inclusive development in modulating the role of governance on environmental degradation. The study focuses on forty-four countries in sub- Saharan Africa for the period 2000-2012. The Generalised Method of Moments is employed as the empirical strategy and CO 2 emissions per capita is used to measure environmental pollution. Bundled and unbundled governance dynamics are employed, notably: political governance (consisting of political stability/no violence and "voice and accountability"), economic governance (encompassing government effectiveness and regulation quality), institutional governance (entailing corruption-control and the rule of law), and general governance (a composite measure of political governance, economic governance and institutional governance). The following main findings are established. First, the underlying net effect in the moderating role of inclusive development in the governance- CO 2 emissions nexus is not significant in regressions pertaining to political governance and economic governance. Second, there are positive net effects from the relevance of inclusive development in modulating the effects of regulation quality, economic governance and general governance on CO 2 emissions. The significant and insignificant effects are elucidated. Policy implications are discussed.
Keywords: C52; O38; O40; O55; P37; 330; CO2 emissions; Governance; Sustainable development; Sub-Saharan Africa